THE EFFECT OF SMOKING ON ULCERATIVE COLITIS - A REVIEW ARTICLE - Kinga Knutelska; Patrycja Jędrzejewska-Rzezak; Monika Czekalska; Natalia Kulicka; Aleksandra Winsyk; Paulina Gajniak; Maciej Karwat; Tytus Tyralik; Klaudia Bilińska; Joanna Węgrzecka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Ulcerative colitis (UC) is an idiopathic, chronic inflammatory disorder of the colonic mucosa. It affects patients’ health and quality of life, and can result in life-threatening complications, such as colon cancer. The aim of the study is to present current knowledge on the impact of cigarette smoking on the onset, course and treatment of ulcerative colitis. Methodology: The authors conducted a comprehensive search of the PubMed electronic database using the keywords. Duplicate studies were removed, and the remaining articles were assessed based on their title and abstract. A total of 20 studies met the inclusion criteria and were subjected to critical review, assessing the methodological design, sample characteristics, and the type and duration of follow-up of the population groups. The primary research for this article was conducted in July 2025. Conclusion: Compared with non-smokers, former smokers have a significantly higher risk of developing ulcerative colitis (UC), and this risk may be proportional to cumulative exposure to tobacco smoke. Based on the presented reports, we can conclude that any potential protective effect is small and observed only in men. The study results do not constitute a basis for justifying cigarette smoking. Combined with numerous other publications in various fields of medicine, primarily oncology and cardiovascular disease, this leads to one clear conclusion: it’s best not to start smoking at all.